Validitas Jobsheet Instalasi Perumahan Berbasis Proyek Berbantuan E-Learning Di Pendidikan Vokasi - Syaiful Islami; Doni Tri Putra Yanto; Oriza Candra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The problem in learning residential houses installations is that the results of student practice are not in accordance with the existing job sheets. Students have difficulty understanding the work steps in the existing job sheet. E-learning is one of the answers to the demands of learning at this time. Therefore, learning media using e-learning is needed. This article aims to test the validity of e-learning-assisted project-based residential houses installation job sheet. The research method used is the mix method. Testing using validity instruments on aspects of content, format and presentation. The analysis used is Aiken's V formula. The results of testing and analysis show that the e-learning-assisted project-based residential houses installation job sheet is valid in the aspects of content, format and presentation.